Vibrational Spectrum and Gas‐Phase Structure of Disulfur Dinitride (S2N2). Issue 33 (14th July 2014) - Perrin, Agnes; Flores Antognini, Andrea; Zeng, Xiaoqing; Beckers, Helmut; Willner, Helge; Rauhut, Guntram
Abstract Gas‐phase FTIR spectra of the ν6 (B‐type) and the ν4 (C‐type) fundamental bands of S2N2 (D2h) were recorded with a resolution of ≤0.004 cm−1 and the vibrational spectrum of S2N2 (D2h) in solid Ar has been revisited. All IR‐active fundamentals and four combination bands were assigned in excellent agreement with calculated values from anharmonic VPT2 and VCI theory based on (explicitly correlated) coupled‐cluster surfaces. Accurate experimental vibrational ground‐ and excited‐state rotational constants of 32S214N2 are obtained from a rovibrational analysis of the ν6 and ν4 fundamental bands, and precise zero‐point average rz (Rz(SN)=1.647694(95) Å, αz(NSN)=91.1125(33)°) and semi‐experimental equilibrium structures (Re(SN)=1.64182(33) Å, αe(NSN)=91.0716(93)°) of S2N2 have been established. These are compared to the solid‐state structure of S2N2 and structural properties of related sulfur nitrogen compounds and to results of ab initio structure calculations.